2003
DOI: 10.1046/j.1475-1313.2003.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of current knowledge on Electronic Vision Enhancement Systems for the visually impaired

Abstract: Magnification can be provided to assist those with visual impairment to make the best use of remaining vision. Electronic transverse magnification of an object was first conceived for use in low vision in the late 1950s, but has developed slowly and is not extensively prescribed because of its relatively high cost and lack of portability. Electronic devices providing transverse magnification have been termed closed-circuit televisions (CCTVs) because of the direct cable link between the camera imaging system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Electronic devices offer some advantages as bigger working distance, higher magnification than conventional devices [5,6]. Nevertheless, more training sessions are required in order to improve the use of these kind of devices.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic devices offer some advantages as bigger working distance, higher magnification than conventional devices [5,6]. Nevertheless, more training sessions are required in order to improve the use of these kind of devices.…”
Section: Discussionmentioning
confidence: 99%
“…Although NEDs have been used as electronic vision enhancement displays for the visually impaired, the number of studies on the use of NEDs for reading tasks or as accessories for enhancement for small-sized displays is limited [62,63,55,36]. Sheedy and Bergstom [55] found a small increase in task performance speed when tasks were performed on near-eye displays compared to flat panel displays and hard copies.…”
Section: Reading From Small-sized Displays and Nedsmentioning
confidence: 99%
“…Electronic Vision Enhancement Systems (EVES) have a great potential to improve perceptual performance of low vision patients [19,20]: in addition to magnification, they can provide many kinds of visual enhancements [21]. A recent survey indicated that most low vision patients express an interest in image processing technology that could be implemented for television viewing and for computer use [22].…”
Section: - Introductionmentioning
confidence: 99%